Performance analysis of single and multiuser MIMO diversity channels using Nakagami-m distribution. - Kai-Kit Wong (IEEE Transactions on wireless communications)
This letter studies the diversity advantage of single and multiuser systems utilizing multiple-input multiple-output (MIMO) antennas for known channels at the transmitter and receiver(s) by investigating the overall distribution of the resulting channel. For the single-user case, the resultant channel is taken as the largest singular value of the MIMO channel whereas for the multiuser scenario, the resultant channel is obtained by a recently proposed joint-channel diagonalization. The channel distribution is studied using hypothesis testing with the hypothesis that the distribution follows a Nakagami-m distribution with given parameters. It is concluded from the chi-square goodness-of-fit test that the distribution of the resultant channel for single or multiuser MIMO channel is well matched with a Nakagami-m distribution.